Analisis Faktor Sosial Ekonomi Petani dalam Adopsi Teknologi Pertanian Presisi untuk Peningkatan Produktivitas Tanaman Pangan di Daerah Agro-Ekologis Tropis - Abdul Rahim Saleh; Nur Zaman; Jeter D Siwalette; Esther Kembauw (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2024)
Introduction: Digital transformation in the agricultural sector has become an urgent need to increase efficiency and productivity, especially in tropical regions that are rich in natural resources but face challenges in adopting technology. Purposed: To analyze the socio-economic factors influencing the adoption of precision agricultural technology by farmers in tropical agro-ecological areas. Research method: A quantitative approach with an explanatory survey design was used in this study, with a sample consisting of crop farmers selected randomly. The independent variables analyzed include age, education, income, land area, access to credit, and participation in farmer groups, while the dependent variable is the level of adoption of precision technology. Results: Logistic regression showed that education, income, access to credit, and participation in farmer groups have a significant impact on the adoption of precision technology. In contrast, land area did not show a significant effect on technology adoption. Access to credit and education had a very strong influence on the adoption decision, followed by income and participation in farmer groups. This study suggests the need for improving access to education, providing adequate financing schemes, and empowering farmer groups to enhance the adoption of precision agricultural technology in tropical areas. Thus, policies supporting precision agriculture technology are expected to improve productivity and sustainability in the region.